2020
DOI: 10.3390/genes11020230
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Aging Effects of Leontopodium alpinum (Edelweiss) Callus Culture Extract through Transcriptome Profiling

Abstract: Edelweiss (Leontopodium Alpinum) in the family Asteraceae is a wildflower that grows in rocky limestone places. Here, we investigated the efficacy of edelweiss callus culture extract (Leontopodium Alpinum callus culture extract; LACCE) using multiple assays from in vitro to in vivo as well as transcriptome profiling. Several in vitro assay results showed the strong antioxidant activity of LACCE in response to UVB treatment. Moreover, LACCE suppressed inflammation and wrinkling; however, moisturizing activity w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 53 publications
(66 reference statements)
2
11
0
Order By: Relevance
“…Therefore, they are expected to be responsible for the effects observed in the in vitro assays that were carried out. The extract also showed strong antioxidant activity as determined through the DPPH free radical scavenging assay, in agreement with previous studies [ 13 , 16 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Therefore, they are expected to be responsible for the effects observed in the in vitro assays that were carried out. The extract also showed strong antioxidant activity as determined through the DPPH free radical scavenging assay, in agreement with previous studies [ 13 , 16 ].…”
Section: Discussionsupporting
confidence: 92%
“…Quantitative analysis of the most abundant four phenylpropanoid derivatives specific to L. alpinum (i.e., chlorogenic acid, 3,5-dicaffeoyl quinic acid, leontopodic acids A and B) ( Table 2 ) revealed that they represent more than 57% (m/m) of the dry-frozen extract and around 15% (m/m) of the dry-frozen callus culture. The measured concentrations of these four constituents in callus culture extracts are comparable or higher than in wild plant [ 16 ] and confirm the high quantity of polyphenols obtained by the total polyphenol content determination. Therefore, they are expected to be responsible for the effects observed in the in vitro assays that were carried out.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Of the six examined parameters of periorbital wrinkles, three (R3 (average roughness), R2 (maximum roughness), and visual assessment)) were significantly different between the treatment and control groups at both 6 and 12 weeks. Our recent study showed the improvement of periorbital wrinkles by Leontopodium Alpinum callus culture extract (LACCE) [ 32 ]. Similarly, a recent study using a cream containing low-molecular-weight heparan sulfate (LMW‐HS) and a mixture of four different naturally derived plant extracts showed the improvement of periorbital wrinkles [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…With a plant-specific bioreactor, it is possible to generate a large quantity of specific plant cells within a short time. Thus, without mature plant cultivation, using the plant callus with a plant-specific bioreactor facilitates the production of diverse plant extracts with a quality equal to that of mature plants [18].…”
Section: Accepted Articlementioning
confidence: 99%